MANAJEMEN LINGKUNGAN BANTARAN KALI BRANTAS BERPENDUDUK PADAT - Nanang Mudjito (Jurnal Teknobisnis, 2005)
The Brantas river sides in Malang City were used for the location of dense human settlement, industrial activities, trades, and other public utilities. Human settlement has grown very rapidly since 2000. This study was aimed to determine a recommendation for environmental management strateg in the Brantas river sides, between Buk Gludug and Alap-alap stretches in particular. The study was performed by direct observation on the river side condition and its uses. A landuse map of 1:2500 scale, a topographical map, and a panchromatic aerial photograph were used. Twentyfour householders were interviewed during this study. Data collected included: history of human settlement growth, land ownership and status, landuse, environmental risks, and use of river sides. Some parts of the river sides in the study area showed soil erosion, which indicated the occurrence of environmental disturbance. The strategy for Brantas river side management should include: human settlement relocation, environmental setting, public education for environmental awareness and entrepreneurships, control of river side uses, and forestation.